Applied Wetlands Science and Technology, 2nd Edition - Kent, Donald M. (CRC Press, 2009)
Continuing the tradition of excellence established by the first edition, the Second Edition of Applied Wetlands Science and Technology provides the fundamentals for delineating, identifying, and regulating wetlands.